Effecting a Transition: How to Fill the Gap in Kant's System of Critical Philosophy - Hall, Bryan (Kant-Studien, 2009)
In a 1798 letter to Christian Garve, Kant claims that without a transition [Übergang] from the metaphysical foundations of natural science to physics there will be a ‘gap’ in the Critical philosophy. He does not make clear, however, exactly what this gap is or how the transition is supposed to fill the gap. The Übergang section of Kant's Opus postumum (OP) has received considerable attention of late due to the many drafts it contains of Kant's Ether Deduction. Commentators have also hoped to find a solution there to the gap problem. Little attention has been paid, however, to Kant's project in Convolut 10 of the OP which he began in August 1799 immediately after completing the Übergang section. Assuming that the Ether Deduction is sound and proves a priori the existence of a transcendental material condition for experience, Convolut 10 discusses what changes would have to be made to the transcendental formal conditions of experience (space, time, categories, and apperception) in their empirical function given the addition of this transcendental material condition. Kant claims in Convolut 10 that these changes are necessary to finally effect a transition from the metaphysical foundations of natural science to physics and, as I will argue, such a transition will be tantamount to bridging the gap in the Critical philosophy mentioned in the letter to Garve.